Practice as research in drama and theatre: Introducing narrative supervision methodology - Aaltonen, Heli; Bruun, Ellen Foyn (Nordic Journal of Art & Research, 2014)
For four decades, the Norwegian University of Science and Technology, NTNU Trondheim, has pioneered the field of drama and theatre in higher education in Norway. This article addresses educational, academic and artistic challenges that emerge when practice as research in the arts enters the academic field of humanities. In particular, the article examines narrative supervision methodology at the master’s level. The first part of the paper identifies the foundations of the contextual and methodological challenges. The main body of the article explores three discussion topics, each illustrated by case examples of practical-theoretical master’s projects. The first example investigates experiential and theoretical borderland tensions; the second addresses onto-epistemic questions; and the third explores the communication of complex narrative construction. Storytelling metaphors are used to advance our emphasis on narrative inquiry as practitioner-researchers and supervisors. The dilemmas outlined are relevant to the Nordic and international community currently navigating this relatively new research area.